Lignin-Assisted Water Electrolysis for Energy-Saving Hydrogen Production With Ti/PbO2 as the Anode - Li, Jiayi; Zhou, Wei; Huang, Yuming; Gao, Jihui (Frontiers in Energy Research, 2021)
Replacing the oxygen evolution reaction (OER), which is of high energy consumption and slow kinetics, with the more thermodynamically favorable reaction at the anode can reduce the electricity consumption for hydrogen production. Here we developed a lignin-assisted water electrolysis (LAWE) process by using Ti/PbO2 with high OER overpotential as the anode aimed at decreasing the energy consumption for hydrogen production. The influence of key operating parameters such as temperature and lignin concentration on hydrogen production was analyzed. Compared with alkaline water electrolysis (AWE), the anode potential can be decreased from 0.773 to 0.303 (V vs. Hg/HgO) at 10 mA/cm2 in LAWE, and the corresponding cell voltage can be reduced by 546 mV. With increasing the temperature and lignin concentration, current density and H2 production rate were efficiently promoted. Furthermore, the anode deactivation was investigated by analyzing the linear sweep voltammetry (LSV) and cyclic voltammetry (CV) tests. Results showed that the anode deactivation was affected by the temperature.